Task Visibility, Free Riding, and Shirking: Explaining the Effect of Structure and Technology on Employee Behavior - Jones, Gareth R. (Academy of Management Review, 1984)
The properties of organized or team production affect three phenomena–free riding, shirking, and task visibility–that mediate the relationship between organizational structure and technology, on the one hand, and employee performance and satisfaction, on the other. Using transaction cost theory, a model of the expected effects of the mediating variables on organizational behavior is presented, and a set of derived hypotheses concerning the structure-technology-behavior relationship is developed.